1989
DOI: 10.1111/j.1423-0410.1989.tb04985.x
|View full text |Cite
|
Sign up to set email alerts
|

Deceptively Low Morbidity from Failure to Practice Safe Blood Transfusion: An Analysis of Serious Blood Transfusion Errors

Abstract: Within a 24-month period, 5 patients in a large teaching hospital were mistakenly transfused with blood that had been crossmatched for different patients. Each of the incidents was due to failure by ward staff to adhere to established safely procedures. Three incidents were entirely due to failure to make the standard checks comparing the identity details on the blood pack label with the patient identification details. The fourth incident was due to a combination of inadequate checking and incomplete patient i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…Audit studies of blood use have identified a number of areas of concern. These arise from system failures, for example inadequate documentation of product use, as well as outcome‐related aspects such as inappropriate administration of products ( Murphy & McClelland, 1989). The hospital population studied in this report comprises most of the acute medical and surgical specialties of large regional hospitals, although it lacks the specialties of cardiac surgery and neonatal intensive care, both of which are traditionally associated with high use of FFP.…”
Section: Discussionmentioning
confidence: 99%
“…Audit studies of blood use have identified a number of areas of concern. These arise from system failures, for example inadequate documentation of product use, as well as outcome‐related aspects such as inappropriate administration of products ( Murphy & McClelland, 1989). The hospital population studied in this report comprises most of the acute medical and surgical specialties of large regional hospitals, although it lacks the specialties of cardiac surgery and neonatal intensive care, both of which are traditionally associated with high use of FFP.…”
Section: Discussionmentioning
confidence: 99%
“…Only a third of unmatched transfusions are incompatible with ABO blood groups; of these, only about a tenth are associated with a fatal outcome 4. We should not, however, be complacent as these figures emphasise that data on mortality and morbidity, even if complete, can give only a substantial underestimate of the incidence of important failures in the transfusion process.…”
Section: Commentmentioning
confidence: 95%
“…[17][18][19][20][21] In transfusion medicine, post-donation information accounts for the majority of events reported by blood and plasma centres to the US Food and Drug Administration (FDA) through a mandatory reporting system, the blood product deviation (BPD) report. 22 The FDA further classifies postdonation information into two categories; information that was known or could have been known at the time of donation, and information not known at the time of the donation.…”
Section: Competency Examination In Taking Health Historiesmentioning
confidence: 99%